Battery diaphragm as well as preparation method and application thereof
By using core-shell microsphere materials with core-shell structure on the lithium-ion battery separator for modified coating, the problems of high density and insufficient heat resistance of the inorganic coating are solved, the electrochemical and thermal stability of the battery is improved, and the electrochemical and thermal stability performance of the battery is simplified. The production process is achieved to achieve lightweight and efficient battery separators.
Patent Information
- Application Number
- CN202411317542.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
AI Technical Summary
The inorganic coating of existing lithium-ion battery separators has problems with high density, poor compatibility, poor particle uniformity and hole blockage. The organic coating lacks heat resistance, resulting in the electrochemical performance, thermal stability and flame retardant performance of the battery. Not good.
Microsphere materials using core-shell structures are used to react polyimidic acid with metal ions in organic solution to form microsphere precursors, and microsphere materials of zirconium oxide, titanium oxide or niobium oxide are obtained by heat treatment, as modified layer Coated on the base film, combined with electrostatic spraying technology and complex-hydrolysis method, the controllable coating and uniform configuration of inorganic microspheres are achieved.
It realizes a low-density, high heat resistance and strong uniformity battery separator, significantly improving the wetting, thermal stability and electrochemical performance of the electrolyte, and the process is simple and easy to perform, suitable for mass production.
Smart Images

Figure CN119297532A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a battery separator and a preparation method and application thereof. Background Art
[0002] In lithium-ion batteries, the separator plays the role of separating the positive and negative electrode materials and avoiding short circuits. Although the separator does not participate in any chemical reaction during the charge and discharge process, it affects the battery's rate, cycle stability and high-temperature safety. At present, the mainstream lithium battery separators used in the market are mainly polyolefin microporous membranes, namely dry-stretched PP membranes, wet-stretched PE membranes, and multi-layer composite membranes of the above two. At present, based on the expansion of a wider range of application fields and the improvement of performance requirements, existing commercial polyolefin microporous membranes are generally difficult to meet related needs. Therefore, in the field of separators, technical upgrades are needed in various aspects such as electrolyte affinity, temperature resistance and pore structure.
[0003] The modification methods of polyolefin separators mainly include: surface irradiation grafting, surface in-situ polymerization, surface electrospinning and surface coating. Among them, surface irradiation grafting is to graft hydrophilic groups such as -OH, -COOH, -NH2 on the surface by physical or chemical methods to improve the hydrophilicity of polyolefin separators. Surface in-situ polymerization generally refers to adding monomers and initiators required for polymerization reaction into the electrolyte, and forming a layer of gel on the surface of the separator through polymerization reaction to improve the electrolyte wettability of polyolefin separators. Surface electrospinning refers to compounding a layer of high heat-resistant polymer non-woven fiber membrane on the polyolefin separator to improve the thermal dimensional stability and electrolyte wettability of the separator. Although the above methods can greatly improve the physical and chemical properties of polyolefin separators, the process is complicated and inefficient in actual production, and industrial production cannot be achieved at present. Correspondingly, the surface coating method refers to coating an organic or inorganic coating on one or both sides of the polyolefin separator to improve the thermal dimensional stability and electrolyte absorption rate of the polyolefin separator. Due to its simple process and high production efficiency, domestic and foreign companies have built multiple production lines for large-scale production of surface coating.
[0004] Specifically, the surface coating method can be divided into inorganic coating and organic coating according to the composition of the coating. Existing inorganic coatings mainly include: Al2O3, SiO2, TiO2, ZrO2, etc.; however, inorganic coatings also have many defects, such as high bulk density, uneven particle size, poor compatibility with polyolefin-based membranes, easy pore blocking, etc. Organic coating can well solve the shortcomings of inorganic ceramic particle coating and improve the electrolyte wettability of the diaphragm. However, the heat resistance of most organic polymer coating materials is still not high enough.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first purpose of the present invention is to provide a battery separator for solving the defects of inorganic coatings due to their own properties, such as high density, poor compatibility with the membrane layer, poor particle uniformity, pore blockage, etc., while solving the defects of organic coatings such as poor heat resistance and insufficient hydrophilicity.
[0007] The second object of the present invention is to provide a method for preparing the battery separator, which is simple and easy to implement and can be easily mass-produced.
[0008] The third object of the present invention is to provide a lithium ion battery, based on the improvement of the separator, so as to improve the electrochemical performance, thermal stability and flame retardancy of the battery.
[0009] A fourth object of the present invention is to provide an electrical device.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] A battery separator, comprising a base film, and a modified layer supported on at least one side of the base film;
[0012] The modified layer comprises a microsphere material with a core-shell structure; the core layer of the microsphere material comprises polyimide, and the shell layer of the microsphere material comprises at least one of zirconium oxide, titanium oxide or niobium oxide.
[0013] A method for preparing the battery separator comprises the following steps:
[0014] (1) Preparation of microsphere material: immersing polyamic acid in an organic solution containing metal ions for a first reaction, and then performing solid-liquid separation to obtain a solid phase component; immersing the solid phase component in water for a second reaction, and performing solid-liquid separation again to obtain a microsphere precursor, and heat-treating the microsphere precursor to obtain a microsphere material;
[0015] (2) Preparation of the modified layer: preparing a uniform slurry containing the microsphere material, coating the slurry on at least one side of the base film, and obtaining a battery separator after a second heat treatment.
[0016] A lithium ion battery comprises the battery separator.
[0017] An electrical device comprises the lithium-ion battery.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present invention constructs an inorganically modified functionalized polyimide (PI) microsphere coating on the surface of the base film, so that it has the advantages of both inorganic coatings and organic coatings, that is, it has the advantages of low density, high heat resistance, strong uniformity, good compatibility with the base film, etc., and further makes the prepared battery separator have the advantages of lightweight, excellent electrolyte wettability, excellent thermal stability, flame retardancy and self-extinguishing properties, etc., which significantly improves the electrolyte wettability, thermal dimensional stability and electrochemical properties of conventional separators.
[0020] (2) The present invention provides a method for preparing a battery separator: first, polyamic acid microspheres are obtained by electrostatic spraying technology, and then a microsphere material with a complete core-shell structure is prepared by a complexation-hydrolysis method, successfully achieving controllable coating of metal oxides on the surface of polyimide microspheres; then, the inorganic microspheres are configured into a water-based slurry and coated on at least one side of the base film to obtain the battery separator. The preparation method of the present invention is simple, easy to operate, low-cost, and can meet the needs of mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 A schematic diagram of the diaphragm structure of the present invention is provided;
[0023] Figure 2 A flow chart of the preparation method of the present invention is provided. DETAILED DESCRIPTION
[0024] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be purchased commercially. In addition, the terms "first", "second" and "third" are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.
[0025] The first aspect of the present invention is to provide a battery separator. The battery separator comprises a base film and a modified layer supported on at least one side of the base film; the modified layer comprises a microsphere material with a core-shell structure; the core layer of the microsphere material comprises polyimide, and the shell layer of the microsphere material comprises at least one of zirconium oxide, titanium oxide or niobium oxide. Figure 1 As shown, taking zirconium oxide as an example, a feasible schematic diagram of the diaphragm structure is provided.
[0026] As a preferred embodiment, the shell layer of the microsphere material includes one of titanium oxide and niobium oxide; or, the shell layer of the microsphere material includes a combination of zirconium oxide and one of titanium oxide and niobium oxide.
[0027] As a preferred embodiment, the base film includes one of a polyethylene film, a polypropylene film or a polyethylene-polypropylene multilayer film; in some more preferred embodiments, a polyethylene (PE) film is selected.
[0028] As a preferred embodiment, the particle size (in terms of diameter) of the microsphere material is 400 nm to 800 nm, including but not limited to any one of 400, 450, 500, 550, 600, 650, 700, 750, 800 (nm) or a numerical range consisting of any two of them.
[0029] As a preferred embodiment, the thickness of the shell layer of the microsphere material is 10 nm to 40 nm, including but not limited to any one of 10, 15, 20, 25, 30, 35, 40 (nm) or a numerical range consisting of any two of them.
[0030] As a preferred embodiment, when the modified layer is loaded on one side of the base film, the thickness of the modified layer is 20 μm to 80 μm; when the modified layer is loaded on both sides of the base film, the thickness of each modified layer is independently selected from 20 μm to 80 μm.
[0031] The second aspect of the present invention is to provide a method for preparing the battery separator. The method mainly includes the preparation of microsphere material and the preparation of modified layer; Figure 2 A feasible preparation process flow chart is shown in FIG. Specifically, the process flow chart includes the following steps.
[0032] (1) Preparation of microsphere material: The polyamic acid is immersed in an organic solution containing metal ions for a first reaction, and then the solid-liquid separation is performed to obtain a solid phase component; the solid phase component is immersed in water for a second reaction, and the solid-liquid separation is performed again to obtain a microsphere precursor, and the microsphere precursor is heat-treated to obtain a microsphere material.
[0033] In this step, the carboxyl groups (—COOH) on the surface of the polyamic acid raw material are complexed with the metal ions in the solution, so that the metal ions are fixed on the surface of the polyamic acid; when the solid phase after the complexation reaction (first reaction) is immersed in water, the metal ions are hydrolyzed again to generate corresponding hydrolysis products on the surface of the polyamic acid; after the hydrolysis reaction (second reaction) is completed, the microsphere precursor is dehydrated and converted by heat treatment, the polyamic acid (PAA) removes intermolecular water and is converted into polyimide (PI), the hydrolysis products of the metal ions are dehydrated and converted into metal oxides, and the metal oxides form the outer shell layer of the polyimide, thereby obtaining a microsphere material with a core-shell structure.
[0034] As a preferred embodiment, the solute of the organic solution containing metal ions includes at least one of zirconium n-butoxide, titanium n-butoxide or niobium n-butoxide, and the solvent of the organic solution containing metal ions includes water.
[0035] As a more preferred embodiment, the mass percentage of the solute in the organic solution containing metal ions is 5% to 15%.
[0036] As a preferred embodiment, the time of the first reaction is 15 min to 60 min; in some more preferred embodiments, the time of the first reaction is 25 min to 35 min.
[0037] As a preferred embodiment, the second reaction time is 30 min to 60 min.
[0038] As a preferred embodiment, the temperature of the heat treatment is 200°C to 400°C, and the time of the heat treatment is 1h to 3h; in some more preferred embodiments, the temperature of the heat treatment is 320°C to 380°C, and the time of the heat treatment is 1h to 1.5h.
[0039] (2) Preparation of the modified layer: preparing a uniform slurry containing the microsphere material, coating the slurry on at least one side of the base film, and obtaining a battery separator after a second heat treatment.
[0040] As a preferred embodiment, the slurry includes the microsphere material, a bonding functional component, a dispersing functional component and a solvent; wherein the bonding functional component includes but is not limited to any one of polyvinylidene fluoride, polyacrylate, methyl cellulose, hydroxymethyl cellulose and its salts, hydroxyethyl cellulose and its salts, hydroxypropyl methyl cellulose and its salts or styrene-butadiene rubber; the dispersing functional component includes but is not limited to any one of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, polyacrylic acid or polyacrylamide; and the solvent includes water and ethanol.
[0041] As a more preferred embodiment, the slurry includes the following components by weight: 6 to 10 parts of the microsphere material, 0.1 to 2 parts of a bonding functional component, 0.1 to 2 parts of a dispersing functional component and 80 to 120 parts of a solvent.
[0042] As a preferred embodiment, the preparation of the slurry includes any one or more of auxiliary means such as oscillation, stirring, ultrasound, centrifugation, heat treatment, etc., and those skilled in the art can achieve uniform dispersion of the components in the slurry through the above means.
[0043] As a preferred embodiment, the temperature of the second heat treatment is 40°C to 80°C, and the time of the heat treatment is 6h to 10h; in some more preferred embodiments, the temperature of the heat treatment is 45°C to 60°C, and the time of the heat treatment is 7h to 9h.
[0044] As a preferred embodiment, the preparation of polyamic acid is also included before step (1), including the following steps: preparing a reaction solution containing pyromellitic anhydride and 4,4'-diaminodiphenyl ether, synthesizing a precursor solution in an ice water bath, and performing electrostatic spraying treatment after aging to obtain a polyamic acid microsphere material.
[0045] That is, in this preferred embodiment, pyromellitic anhydride (PMDA) and 4,4'-diaminodiphenyl ether (ODA) are used as polymerization monomers to obtain a precursor solution containing polyamic acid after polymerization; then, an electrostatic spray liquid with a suitable viscosity is obtained through aging, and a microspherical polyamic acid material is obtained through an electrostatic spray process, which is suitable as the core layer of the subsequent microspherical material.
[0046] As a more preferred embodiment, the molar ratio of the pyromellitic anhydride to the 4,4'-diaminodiphenyl ether is 1.01:1. In actual operation, the amount of the pyromellitic anhydride is slightly higher than that of the 4,4'-diaminodiphenyl ether. The preparation is also based on the molar ratio of dianhydride to diamine.
[0047] As a more preferred embodiment, the aging temperature is 40°C to 80°C, and the aging duration is 45h to 50h; in some more preferred embodiments, the aging temperature is 50°C to 70°C, and the aging duration is 47h to 49h.
[0048] As a more preferred embodiment, the kinematic viscosity of the aged solution is 100 cP to 200 cP.
[0049] As a more preferred embodiment, the reference parameters of the electrostatic spray are set as: positive pressure of 20 kV, negative pressure of 5 kV, and receiving distance between the nozzle and the substrate of 18 cm. It is understandable that if there are other ways to prepare microspherical polyamic acid from the precursor solution, the electrostatic spray can also be replaced.
[0050] The third aspect of the present invention is to provide a lithium-ion battery. The lithium-ion battery includes the battery separator. It is understandable that, in addition to the battery separator, the lithium-ion battery should include a positive electrode, a negative electrode, an electrolyte, and other necessary or unnecessary functional elements or packaging components, etc., and those skilled in the art can make any selection and combination thereof; when the battery separator of the present invention is included in the lithium-ion battery, whether or not other membrane functional elements are also used in combination in the lithium-ion battery, it can be regarded as an embodiment of the present invention.
[0051] The fourth aspect of the present invention is to provide an electric device. The electric device includes the lithium-ion battery. The electric device can be any device or apparatus that relies on electric energy to work or operate, including but not limited to new energy vehicles, building electrical equipment, industrial electrical appliances, household and agricultural electrical appliances, etc.; when including the lithium-ion battery, any electric device equipped with the lithium-ion battery can belong to an embodiment of the present invention.
[0052] Example 1
[0053] S1. Preparation of polyamic acid microspheres:
[0054] The polymerization monomers are selected as pyromellitic anhydride and 4,4'-diaminodiphenyl ether, and DMF is used as a polar solvent. A precursor solution with a solid content of 15% is synthesized in an ice-water bath according to the molar ratio of dianhydride:diamine=1.01:1; the polyamic acid solution is obtained after aging at a constant temperature of 60°C for 48 hours; and the polyamic acid solution is electrostatically sprayed according to the parameters of positive pressure 20kV, negative pressure 5kV, and a receiving distance of 18cm from the substrate to obtain polyamic acid microspheres.
[0055] S2. Preparation of microsphere materials:
[0056] The polyamic acid microspheres prepared above were immersed in a 5wt.% zirconium n-butoxide solution for 30 minutes, and then the filtered microspheres were placed in deionized water for 30 minutes, and finally heated at 360°C in a forced air oven for 1.5 hours to obtain ZrO2@PI-5% microsphere material with a core-shell structure.
[0057] S3, microsphere coated modified polyethylene diaphragm:
[0058] Weigh 8wt.% of the microsphere powder prepared above, 0.6wt.% of polyvinyl pyrrolidone, and 0.6wt.% of sodium carboxymethyl cellulose and add them to a mixed solvent of water and anhydrous ethanol (volume ratio of 1:1), ultrasonically disperse for 30 minutes to obtain a slurry without obvious coagulation, and stir it with a magnetic stirrer at a speed of 1500r / min for 4 hours to obtain a homogeneous microsphere slurry. Then, it is coated on a PE base film with a gap of 50μm on an automatic scraper coater, and then placed in a blast oven at 50°C for 8 hours to obtain a microsphere-coated modified polyethylene diaphragm.
[0059] Example 2
[0060] It is basically the same as Example 1, except that the concentration of the zirconium n-butoxide solution in step S2 is 15wt.%, and a ZrO2@PI-15% microsphere material with a core-shell structure is obtained in step S2.
[0061] Example 3
[0062] The method is basically the same as Example 1, except that the zirconium n-butoxide solution is replaced with titanium n-butoxide solution in step S2, and a TiO2@PI-5% microsphere material with a core-shell structure is obtained in step S2.
[0063] Example 4
[0064] The method is basically the same as Example 1, except that the zirconium n-butoxide solution is replaced with niobium n-butoxide solution in step S2, and a Nb2O5@PI-5% microsphere material with a core-shell structure is obtained in step S2.
[0065] Example 5
[0066] It is basically the same as Example 1, except that:
[0067] The heat treatment in step S2 is replaced by: heating at 200°C for 3h in a forced air oven;
[0068] The heat treatment in step S3 is replaced by: drying in a forced air oven at 40° C. for 10 h.
[0069] Example 6
[0070] It is basically the same as Example 1, except that:
[0071] The heat treatment in step S2 is replaced by: heating at 400°C in a forced air oven for 1 h;
[0072] The heat treatment in step S3 is replaced by: drying in a forced air oven at 80°C for 6 hours.
[0073] Test Example 1: Wettability Verification
[0074] In order to verify the wetting effect of the microsphere material prepared in each embodiment, the electrolyte wetting rate and contact angle test were performed on the diaphragm and PE base film prepared in each embodiment (i.e., the comparative example in Table 1 below). The specific operation is to drop the electrolyte in the center of the above diaphragm and observe the spreading of the electrolyte after 10s; the composition of the electrolyte used here is: EC28.85wt%, DMC 20.27wt%, EA 37.09wt%, LiPF6 9.17wt%, LiFSI 4.62wt%.
[0075] The test results of this test example are shown in Table 1 below.
[0076] Table 1
[0077]
[0078]
[0079] Test Example 2: Verification of porosity, liquid absorption, air permeability, and surface density
[0080] In this test example, a PE base film is selected as a comparison (Comparative Example 1), and a commercial Al2O3 coated PE diaphragm is selected as a comparison (Comparative Example 2). The test results of this test example are shown in Table 2 below.
[0081] (1) The evaluation method of liquid absorption rate includes: weighing 3 50mm*50mm diaphragm samples to an accuracy of 0.01g; immersing them in a beaker containing electrolyte (the electrolyte composition is the same as that in Test Example 1), and after immersing them in the electrolyte for 10 minutes, gently clamping a corner of the sample with plastic tweezers, taking it out, suspending it in the air for 3 minutes to drip off the electrolyte, and then weighing them separately to an accuracy of 0.01g; the formula for calculating the liquid absorption rate is (m1-m) / m*100%, where m is the numerical value of the mass of the sample before immersion, and m1 is the numerical value of the mass after immersion.
[0082] (2) The porosity is evaluated by the pressure pump method and its supporting equipment, and the porosity is obtained by testing.
[0083] (3) The air permeability is evaluated by using a membrane air permeability tester; three membranes are cut from the membrane roll at an interval of 150 mm in the longitudinal direction, and the sampling size is 100 mm*membrane width; the membrane is placed in the instrument for air permeability testing, and the average value of the three test results is taken as the air permeability of the membrane.
[0084] (4) The evaluation method of the surface density includes: weighing three 50 mm*50 mm diaphragm samples with an accuracy of 0.01 g; measuring the diameters of the three samples respectively, calculating the area, dividing the mass by the area to obtain the surface density, and taking the average value of the three measurements.
[0085] Table 2
[0086]
[0087] As can be seen from Table 2, the presence of the microsphere coating of the present invention and the conventional alumina coating increases the porosity of the base film, and the liquid absorption rate also changes in a consistent pattern with the porosity; however, another reason for the significant difference in liquid absorption between the microsphere coating of the present invention and that of Comparative Example 2 is that the weight of the diaphragm itself is lower. As for air permeability, the coatings of the present invention and Comparative Example 2 both cause a slight increase in air permeability, but since the pores between the microspheres of the present invention are larger than those of Comparative Example 2, the value of the increase in air permeability of the diaphragm of the present invention is smaller than that of the diaphragm of Comparative Example 2, which is also consistent with the law of porosity change. In addition, at the same coating thickness, the surface density of the diaphragm of the present invention is only half of that of Comparative Example 2, and the surface density of the microsphere coating of the present invention is only one-third of the coating density. The lower surface density is conducive to reducing the weight of the lithium battery, thereby improving the overall energy density.
[0088] Furthermore, since the PE material itself has the characteristics of non-polar surface and low surface energy, the wettability of the PE diaphragm to the electrolyte is poor; while the inorganic layer on the surface of the microspheres of the present invention contains many polar groups, has good affinity for the electrolyte, and the microspheres are tightly packed to form a three-dimensional pore structure, which is more conducive to the infiltration of the electrolyte. Therefore, in terms of porosity, liquid absorption rate, and air permeability, the pores of the diaphragm itself of each embodiment of the present invention are larger than those of the diaphragm of Comparative Example 1, and the uniform particle size and particle size distribution of the microsphere material result in more gaps between the microspheres, so the physical properties are improved compared to the PE diaphragm.
[0089] Test Example 3 Electrochemical Test
[0090] The ternary NCM811 system was selected as the positive electrode material, and the Li sheet was used as the negative electrode to assemble a button half-cell. The electrolyte composition was the same as that of Test Example 1 to simulate the actual performance of the diaphragm of each embodiment in the battery. Similarly, a PE base film (i.e., the comparative example in Table 3 below) was selected for the same assembly as a control. The capacity of each button half-cell was tested, and the test results of this test example are shown in Table 3 below. As can be seen from Table 3, the diaphragm of each embodiment of the present invention has obvious improvements in battery capacity performance compared to conventional PE films.
[0091] Table 3
[0092] Capacity (mAh / g) Example 1 208.1 Example 2 212.3 Example 3 198.4 Example 4 203.2 Example 5 208.5 Example 6 209.6 Comparative Example 195.3
[0093] Test Example 4 Thermal Stability Test
[0094] Thermal stability is an important indicator to measure the thermal safety performance of the diaphragm. Conventional PE diaphragms have a low melting point and will shrink severely at 150°C and become transparent. Their original microporous structure is destroyed and they will completely melt and shrink into a ball at 180°C. Therefore, batteries assembled with PE diaphragms will cause battery short circuits at high temperatures, causing serious safety hazards.
[0095] Correspondingly, taking the diaphragm prepared in Example 1 as an example, it hardly shrinks at 150°C, and only slightly curls at the edges. When heated to 180°C, it still maintains a low shrinkage, thereby ensuring the safety performance of the battery at high temperatures.
[0096] The organic electrolyte, one of the important components of lithium-ion batteries, is extremely flammable, especially when the battery is short-circuited and thermally runaway, it is often accompanied by explosions and fires, posing a great threat to the daily use of the battery. The PE diaphragm shrinks rapidly and burns violently after being ignited by an open flame, and continues to burn into ashes after the fire source leaves. The diaphragm prepared in Example 1 shrinks and burns after being ignited by an open flame, but the burning flame is small and slow, and automatically extinguishes when the fire source leaves. Compared with the PE diaphragm, the diaphragm prepared in Example 1 has excellent flame retardant and self-extinguishing properties, can reduce the impact of local hot spots caused by dendrite lithium on safety performance, and delay the time from short circuit to open flame explosion of the battery, which is very beneficial to improving the safety performance of the battery.
[0097] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A battery separator, characterized in that: The battery separator includes a base film and a modified layer supported on at least one side of the base film; The modified layer comprises a microsphere material with a core-shell structure; the core layer of the microsphere material comprises polyimide, and the shell layer of the microsphere material comprises at least one of zirconium oxide, titanium oxide or niobium oxide.
2. The battery separator according to claim 1, characterized in that: The particle size of the microsphere material is 400nm to 800nm; And / or, the shell layer of the microsphere material has a thickness of 10 nm to 40 nm.
3. The battery separator according to claim 1, characterized in that: The thickness of the modified layer is 20 μm to 80 μm.
4. The method for preparing a battery separator according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Preparation of microsphere material: immersing polyamic acid in an organic solution containing metal ions for a first reaction, and then performing solid-liquid separation to obtain a solid phase component; immersing the solid phase component in water for a second reaction, and performing solid-liquid separation again to obtain a microsphere precursor, and heat-treating the microsphere precursor to obtain a microsphere material; (2) Preparation of the modified layer: preparing a uniform slurry containing the microsphere material, coating the slurry on at least one side of the base film, and obtaining a battery separator after a second heat treatment.
5. The method for preparing a battery separator according to claim 4, characterized in that: The method further includes the following steps before step (1): The preparation of the polyamic acid comprises preparing a reaction solution containing pyromellitic anhydride and 4,4'-diaminodiphenyl ether, synthesizing a precursor solution in an ice water bath, and performing electrostatic spraying treatment after aging to obtain the microsphere material of the polyamic acid.
6. The method for preparing a battery separator according to claim 4, characterized in that: In step (1), the solute of the organic solution containing metal ions includes at least one of zirconium n-butoxide, titanium n-butoxide or niobium n-butoxide, and the solvent of the organic solution containing metal ions includes water.
7. The method for preparing a battery separator according to claim 4, characterized in that: The temperature of the heat treatment is 200°C to 400°C, and the time of the heat treatment is 1h to 3h; And / or, the temperature of the second heat treatment is 40° C. to 80° C., and the time of the heat treatment is 6 h to 10 h.
8. The method for preparing a battery separator according to claim 4, characterized in that: In step (2), the slurry includes the microsphere material, a bonding functional component, a dispersing functional component and a solvent; Preferably, the bonding functional component includes at least one of polyvinylidene fluoride, polyacrylate, methyl cellulose, hydroxymethyl cellulose and its salts, hydroxyethyl cellulose and its salts, hypromellose and its salts, or styrene-butadiene rubber; Preferably, the dispersing functional component comprises at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, polyacrylic acid or polyacrylamide; Preferably, the solvent comprises water and ethanol.
9. A lithium ion battery, characterized in that: The lithium ion battery comprises the battery separator according to any one of claims 1 to 3.
10. An electrical device, characterized in that: The electrical device comprises the lithium-ion battery as claimed in claim 9.
Citation Information
Patent Citations
Polyimide / titanium dioxide composite microsphere and preparation method thereof
CN113956658A
Organic-inorganic composite microsphere, battery diaphragm, preparation method of organic-inorganic composite microsphere, preparation method of battery diaphragm and battery
CN114874465A
Novel polyimide / zirconium dioxide composite nanosphere slurry and coated diaphragm thereof
CN115911745A
A slurry composition and a lithium-ion battery separator comprising the same
KR1020160012083A